ChemInform Abstract: Ammonia Synthesis by N2 and Steam Electrolysis in Molten Hydroxide Suspensions of Nanoscale Fe2O3. Issue 43 (21st October 2014) - Licht, Stuart; Cui, Baochen; Wang, Baohui; Li, Fang‐Fang; Lau, Jason; Liu, Shuzhi
Abstract Ammonia is produced by electrolysis of air and steam in a molten 0.5NaOH/0.5KOH suspension of nano‐Fe2O3 (200 °C, 1.2 V, 2 mA/cm2, 35% coulombic efficiency).